A New ent-kaurene Diterpenoid Isolated from Leaves of Espeletia semiglobulata Cuatrec. and its Potential Antimicrobial Activity - Alida Perez; Luis Rojas; Rosa Aparicio; Freddy Ramos; Ysbelia Obregon; Alfredo Usubillaga; Andres Marquez (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
The fraction of the neutral extraction of the leaves of Espeletia semiglobulata Cuatrec. was subjected to chromatographic separation, it yielded four ent-kaurene type diterpenoids: three known [ent-kaur-16-en-19-al (I), ent-kaur-18-nor-16-en-4-ol (III), ent-kaur-16-en-19-ol (IV)] and a new one elucidated as ent-kaur-3-acetoxy-15-ene (II), based on the physicochemical and spectroscopic data of FTIR, GC-MS, and 1D and 2D NMR. These compounds were subjected to antimicrobial bioassay studies. This new ent-kaurene showed a significant inhibition potential against the growth of gram negative bacterial strains [Escherichia coli (ATCC 25922): 8 mm, Klebsiella pneumoniae (ATCC 23357): 10 mm, Pseudomonas aeruginosa (ATCC 27853): 8 mm], it also showed inhibition against the growth of fungal strain (Candida krusei: 8 mm), at a 2 mg/mL concentration. The compounds (I), (III) and (IV) failed to show any significant results in the antimicrobial screening against five bacterial strains [Staphylococcus aureus (ATCC 25923), Enterococcus faecalis (ATCC 29212), Klebsiella pneumoniae (ATCC 23357), Escherichia coli (ATCC 25922) y Pseudomonas aeruginosa (ATCC 27853)] and one fungal strain [Candida krusei (ATCC 6558)]. These results reveal a remarkable natural structure-activity relationship of the ent-kaurene core regarding the C-3 position (A ring of perhydrophenanthrene unit), whose oxygenation or addition of a hydrogen bond acceptor or donor group, improves the antimicrobial activity.